Introduced honey bees (Apis mellifera) potentially reduce fitness of cavity-nesting native bees through a male-bias sex ratio, brood mortality and reduced reproduction - Prendergast, Kit; Murphy, Mark V.; Kevan, Peter G.; Ren, Zong-Xin; Milne, Lynne A. (Frontiers in Bee Science, 2025)
IntroductionIn Australia, as well as many other regions of the world, European honey bees Apis mellifera are an introduced species and may harm native bee fauna by competing with them for food resources. Field studies have revealed negative associations between honey bee and native bee abundance, but whether this translates to fitness costs for native bees is unclear.MethodsUsing drilled wooden-block trap nests, we evaluated whether honey bee abundance is associated with fitness parameters (number of nests, provisioned cells per nest, offspring number, mortality rate, sex ratio, and body size) of cavity-nesting native bees over 2 years. We also conducted palynological analyses to measure pollen resource overlap and evaluate whether this impacts native bee fitness.Results and discussionGreater honey bee abundance was associated with a male-biased sex ratio in the native bee progeny across years and an increased mortality rate of native bee progeny in the first year. Most non-significant associations were also in the directions predicted from honey bees adversely impacting native bee fitness. In the first year, greater pollen morphospecies overlap was associated with fewer provisioned cells. In conclusion, we demonstrated that honey bees have the potential to have harmful consequences for native bee fitness.